PERSAINGAN USAHA YANG SEHAT DALAM PENYELENGARAAN HAJI DI INDONESIA (Prespektif Hukum Persaingan Usaha dan Anti Monopoli) - Muhammad Shidqon Prabowo (Qistie Jurnal Ilmu Hukum, 2011)
The implementation of Indonesian Hajj pilgrimage has been arranged throughthe State Constitution Law No. 17 Year 1999 about the implementation of hajj,which has generated by the Indonesian House of Representatives through thecommission VIII. Improvement initiative that deserves its appreciation from allparties in order to achieve optimal service hajj operation as one of manifestationof state accountability in ensuring the independence of each of its citizens to runtheir religion and belief, as has been mandated by the Constitution 45.However, the provisions in the bill as it has generated by the House is stillmaintaining the paradigm that in order to guarantee protection of the state mustmanifested in the from of dual functions of regulation and functionimplementation by the government. Monopolisme management which has beenrun at least sufficient to provide the information that such a pattern has resulted inthe implementation of the pilgrimage is not optimal and there should beharmonization between the government as the organization of the pilgrimage withthe private sector so that the good cooperation established.Keywords: Competition, Implementation of Hajj in Indonesia.